Pola Asuh Dalam Keluarga Polri di Asrama Polisi Toddopuli Kota Makassar - Nur, Hasruddin; Abdullah, Aditya (Universitas Negeri Makassar, 2021)
This study aims to (1) find out what parenting styles are used in households in the families of the police who live in the Toddopuli Police Dormitory, Makassar City, (2) To determine the time allocation in the police family between work, family and children, (3) To find out the impact of implementing a parenting style. This type of research is a descriptive qualitative research. Techniques to collect data used were observation, documentation and in-depth interviews with informants and involved 5 families consisting of 3 people, namely father, mother and one child. Requirements for a resource are that both parents are police officers, children who are old enough to provide information, thus we use purposive sampling as a method for sorting out potential informants. Meanwhile, the data validation technique uses source triangulation. The results of this study indicate that (1) the number of factors that influence a parenting style used in the family is the reason that the police family living in the Toddopuli Police Dormitory uses mixed and situational parenting styles as parenting styles that are considered appropriate in raising and caring for their children. (2) This allocation is divided into three, namely work, family and children. However, the facts found in this time division show that wives still have a bigger role than husbands despite the patriarchal concept that is still widely used in Indonesia. (3) the impact of the adoption of this parenting style can also be divided into two parts where the parenting influences the child's personality in the family and their social environment, which of course has a positive and negative impact.